Disruption of spatio-temporal processing in human vision using transcranial magnetic stimulation - Stevens, Laura Kate (2009)
Transcranial magnetic stimulation (TMS) is a non-invasive technique used to reversibly modulate the activity of cortical neurons using time-varying magnetic fields. Recently TMS has been used to demonstrate the functional necessity of human cortical areas to visual tasks. For example, it has been shown that delivering TMS over human visual area V5/MT selectively disrupts global motion perception. The temporal resolution of TMS is considered to be one of its main advantages as each pulse has a duration of less than 1 ms. Despite this impressive temporal resolution, however, the critical period(s) during which TMS of area V5/MT disrupts performance on motion-based tasks is still far from clear.